ISOLASI DNA METAGENOMIK DARI MADU DENGAN DAN TANPA PENGAYAAN MEDIA LB (Luria-Bertani) - Hartawan, I Gusti Ngurah Bagus Andre; Arsa, Made; Ariati, Ni Komang; Wirajana, I Nengah (Jurnal Kimia (Journal of Chemistry); Vol. 9, No. 2 Juli 2015DO - 10.24843/JCHEM.2015.v09.i02.p08, 2015)
DNA content in total honey microorganism can be used to study DNA fingerprint of honey. Metagenomic is a new approach to analyse complex genomes from unculturable total microorganism. The aim of this research was to get DNA metagenomic isolated directly from honey samples enriched with microorganisms growing media LB (Luria-Bertani) and without enrichment of microorganisms growing media LB in order to study DNA fingerprint of honey for the next research. The study was started with incubation of the LB enriched honey samples and honey without LB samples at variation time of 0, 24, 48, and 72 hours. Following the incubation process, the DNA metagenomic form both LB enriched and unenriched honey samples were isolated with direct cell lysis method. The DNA obtained was analyzed by spectrophotometer UV-Vis and agarose gel electrophoresis.  The result showed that DNA metagenomic can be isolated from LB enriched honey and without LB enriched honey samples. Analysis using the agarose gel electrophoresis indicated that the metagenomic DNA obtained from both honey samples was still contaminated with RNA. The purity ratio of metagenomic DNA from both honey samples analysed using UV-Vis Spectrophotometer at ? 260/280 nm was between 1.2 to 1.6. This ratio suggested that the metagenomic DNA isolated from both samples were contaminated with protein and fenol.
Keywords: Honey, DNA, Metagenomic